Cloning and Heterologous Expression of a Large-sized Natural Product Biosynthetic Gene Cluster in Streptomyces Species - Nah, Hee-Ju; Pyeon, Hye-Rim; Kang, Seung-Hoon; Choi, Si-Sun; Kim, Eung-Soo (Frontiers in Microbiology, 2017)
Actinomycetes family including Streptomyces species have been a major source for the discovery of novel natural products (NPs) in the last several decades thanks to their structural novelty, diversity and complexity. Moreover, recent genome mining approach has provided an attractive tool to screen potentially valuable NP biosynthetic gene clusters (BGCs) present in the actinomycetes genomes. Since many of these NP BGCs are silent or cryptic in the original actinomycetes, various techniques have been employed to activate these NP BGCs. Heterologous expression of BGCs has become a useful strategy to produce, reactivate, improve, and modify the pathways of NPs present at minute quantities in the original actinomycetes isolates. However, cloning and efficient overexpression of an entire NP BGC, often as large as over 100 kb, remain challenging due to the ineffectiveness of current genetic systems in manipulating large NP BGCs. This mini review describes examples of actinomycetes NP production through BGC heterologous expression systems as well as recent strategies specialized for the large-sized NP BGCs in Streptomyces heterologous hosts.